2018
DOI: 10.1021/acssuschemeng.8b01475
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Water Resistance of Hemp Woody Substrates through Deposition of Functionalized Silica Hydrophobic Coating, While Retaining Excellent Moisture Buffering Properties

Abstract: degree qualification. I confirm that the work is my own, and where some work was carried out as part of a collaborative project, contributors are explicitly mentioned and acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…Therefore, there is a need to develop new hemp based composites to address the existing issues as well as to retain the maximum insulating and moisture buffering properties of the bio-based aggregate. The use of silica based coatings on hemp shiv has proven to be successful in enhancing its hydrophobicity [19,20]. Application of silica based coatings have successfully shown to lower the water absorption capacity of hemp shiv yet retaining its moisture buffering ability due to presence of small pores that are not blocked by the coating [21,22].…”
mentioning
confidence: 99%
“…Therefore, there is a need to develop new hemp based composites to address the existing issues as well as to retain the maximum insulating and moisture buffering properties of the bio-based aggregate. The use of silica based coatings on hemp shiv has proven to be successful in enhancing its hydrophobicity [19,20]. Application of silica based coatings have successfully shown to lower the water absorption capacity of hemp shiv yet retaining its moisture buffering ability due to presence of small pores that are not blocked by the coating [21,22].…”
mentioning
confidence: 99%
“…Silica and TEOS are coating material compositions, applied to the surface treatment of hemp fiber composites. Then the result of this study found that the water contact angle is 120℃ [11] . This study aims to determine the physical and mechanical properties of rice straw hydrophobic composites and the effect of volume fraction and alkalization treatment on fiber.…”
Section: Introductionmentioning
confidence: 81%
“…While the surface that has been coated with a hydrophobic layer has little contact between water and the substrate. Water droplets on the surface of the straw epoxy hydrophobic composite have a water contact angle more than 90 o C which is the minimum contact angle value for a hydrophobic surface [11] . In the roll coating method, it seems to be able to hold water droplets and no droplets seep.…”
Section: Cellulose Contentmentioning
confidence: 96%
“…The readings were taken at frequent intervals for 24 hours, in which the sample was taken out of water using a tweezer, shaken off to remove any visible surface water and then weighed within 30s. Mass readings were recorded to the nearest 0.1 mg and an average of three readings from different samples was reported as the final measurement [24,25].…”
Section: Water Absorption Testmentioning
confidence: 99%